Investigation of the MFS drug transporter family in Candida parapsilosis using CRISPR-Cas9. Issue 12 (17th December 2021) - Zhao, Fang; Butler, Geraldine
Abstract : The function of specific transporters is a key feature underlying drug resistance in Candida species. Drug transporters fall into two main classes – ATP-binding cassette (ABC) transporters, and the major facilitator superfamily (MFS) transporters. Some members of the drug/H (+) antiporter (DHA1) of the MFS superfamily have been shown to function as multidrug transporters. We targeted 16 genes belonging to five families that compose one branch of the DHA1 transporter group. These include MDR1/FLR1, associated with multidrug resistance in C. albicans (3 members); TPO4, associated with polyamine transport (1 member); NAG3/4, associated with transport of N-acetyl glucosamine (2 members); TPO2/3, associated with polyamine transport (1 member); and TPO1/FLU1, possibly associated with fluconazole resistance (9 members). We used CRISPR-Ca9 based gene editing to explore the function of of the five families in C. parapsilosis . All 16 members were individually disrupted by introducing stop codons in the first third of the open reading frames (editing), or by deleting the whole gene. In addition, members of each family were disrupted together, including all 9 members of the TPO1/FLU1 family. CPAR2_603010, CPAR2_207540, and CPAR2_301760 all belonged to the MDR1 family. Editing CPAR2_603010 conferred sensitivity to fluconazole and voriconazole, though disrupting the other two genes had no effect. The azole sensitivity of the CPAR2_603010 edited strain was reverted by introducing the wild type sequence. Disrupting CPAR2_603010 or CPAR2_301760 individually did not affect sensitivity to 4-nitroquinoline 1-oxide. However, the double disruptant was sensitive. Disrupting CPAR2_300760, a member of the TPO1/FLU1 family, resulted in sensitivity to mycophenolic acid. Whole genome sequencing analysis of a strain in which all nine TPO1 genes were disrupted revealed that few off-target effects introduced by the CRISPR-Cas9 system, as few unexpected changes were found after eight rounds of transformation.